TrivPlat - A monitoring, management and evaluation tool for electronic public procurement - Ferreira, Isabel (2018)
Bad decisions in public procurement processes have two negative effects: price increase of public goods and services with an impact on public expenditure, and adversely effects on competition, with the negative result of loss of efficiency and social welfare. Electronic public procurement (EPP) has been considered an important tool for promoting competition, simplifying and ensuring transparency in decision-making processes, thus ensuring significant time and money gains. In Portugal, EPP replaced paper-based pre-contractual procedures for communication and processing based on information technologies and systems. Interested in this phenomenon, the authors of this paper structured the TrivPlat project, a tool of free access for monitoring, managing and evaluating electronic public procurement. This paper aims to present the TrivPlat project and its contributions to the discussion about additional efforts needed to be implemented in order to efficiently promote a more transparent and accountable governance, in the defense of public interest.